Association of T2 mapping of knee cartilage with age, gender & BMI among young adults attending Pusat Pengimejan Diagnostik Nucklear (PPDN), Universiti Putra Malaysia - Soo, Tze Hui (2021)
According to World Health Organization, osteoarthritis (OA) is defined as a long-term chronic disease characterized by deterioration of joints cartilage as a sequelae of degenerative changes causing stiffness, pain and impaired mobility. The disease most commonly affects the joints in the knees, hands, feet, and spine and is relatively common in shoulder and hip joints. The prevalence of knee OA in Malaysia was estimated to be 10% to 20% of the elderly population and more common in adults aged 40 years and above. Self-regeneration processes are only initiated when damage reaches the subchondral bones. Sudden and rapid applied excessive force would not allow for sufficient fluid to move through the matrix for shock absorption, thus allowing the stress to be applied fully on the macromolecules network causing micro tears and matrix injury. In severe cases, there might be segmental loss of cartilage. Macromolecules synthesized by chondrocytes are inadequate to fill the gaps caused by injuries. By times, OA start to set in causing chronic pain and instability. MRI is the only imaging of choice that able to provide structural details as well as biochemical information about the articular cartilage. Moreover, it would be desirable for MRI to provide an evaluation of the underlying cartilage physiology including providing information about the status of prostaglandins (PGs) and collagen matrices. T2 mapping is straightforward to perform and is sensitive to changes in collagen as well as water content, but less sensitive in detection of early degeneration. A retrospective and prospective cross sectional study using secondary and primary data to provide information on the value of T2 mapping of knee articular cartilage (medial and lateral compartment) in asymptomatic young adult and its association with gender, age and body mass index was carried out over a period of 2 years from December 2018 to December 2020. The data was then post processed with T2 mapping programming via Matlab R2019b version and further analysed with SPSS version 26. Overall, we has shown that female has slightly higher mean T2 value (49.1731ms to 51.9192ms) as compared to male population (48.4147ms to 49.4647ms) out of 30 volunteers recruited. We concluded that as we age, the T2 value increases which signify the occurrence of OA has set in slowly. In our study, T2 value increases as BMI increase as well. With 3 independent variables tested, our result were consistent with previous studies even though there was no strong association ( p > 0.05) obtained.